2010
DOI: 10.1177/1082013209353223
|View full text |Cite
|
Sign up to set email alerts
|

Foaming and Emulsifying Properties of Porcine Red Cell Protein Concentrate

Abstract: This work focuses on studying the effects of pH (7.0 and 4.5) and protein concentration on the foaming and emulsifying properties of fresh (F) and spray-dried (SD) porcine red cell protein (RCP) concentrates in order to evaluate the proper use of this blood protein as a functional food ingredient. Also, protein solubility is measured through the pH range from 3.0 to 8.0. In each case, all concentrates show a high solubility, although this is significantly affected by pH. Spray drying slightly reduces the solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…However, temperature >60 °C is not recommended. Rustom et al. (1991) also reported that the increase in temperature from 20 to 60 °C would decrease the extracted protein.…”
Section: Resultsmentioning
confidence: 95%
“…However, temperature >60 °C is not recommended. Rustom et al. (1991) also reported that the increase in temperature from 20 to 60 °C would decrease the extracted protein.…”
Section: Resultsmentioning
confidence: 95%
“…Blood, which accounts for approximately 7% of the total weight of a pig, contains 75-80% moisture and 15-17% high-quality protein (albumin, globulin, and hemoglobin) [6,7]. Despite its potential as a bioresource, blood is disposed of due to a lack of research on possible industrial uses and a general aversion.…”
Section: Pwbph Increases Endurance Performance and Relative Muscle We...mentioning
confidence: 99%
“…Blood, which accounts for approximately 7% of the total weight of a pig, contains 75-80% moisture and 15-17% high-quality protein (albumin, globulin, and hemoglobin) [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 2.5-3.0 L of blood per pig, amounting to approximately 39,216 tons per year, has a major impact on water pollution [1,2]. Blood, which accounts for approximately 7% of the total weight of pigs, generally contains 75-80% moisture and 15-17% high-quality protein; the protein is composed of albumin, globulin, and hemoglobin [3,4]. Although this blood has the potential to become a valuable bioresource, it is disposed of due to a lack of research on possible industrial uses and a general aversion to blood.…”
Section: Introductionmentioning
confidence: 99%